1999
DOI: 10.1136/bjsm.33.4.281
|View full text |Cite
|
Sign up to set email alerts
|

Late repair of simultaneous bilateral distal biceps brachii tendon avulsion with fascia lata graft.

Abstract: A 50 year old rock climber sustained a bilateral rupture of the distal biceps brachii tendons. He retained some flexion power in both arms but minimal supination, being weaker on the non-dominant right side. As the patient presented late, with retraction and shortening of the biceps muscle bellies, reconstruction was carried out using fascia lata grafts on both sides. Because of residual weakness on the left (dominant) side, three further surgical procedures had to be carried out to correct for elongation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…The current literature reflects good functional outcome with numerous different graft sources. 13,16,17,19,[22][23][24][25] But, further research is needed to determine the optimal treatment for reconstruction of chronic distal bicep tendon ruptures. …”
Section: Resultsmentioning
confidence: 98%
“…The current literature reflects good functional outcome with numerous different graft sources. 13,16,17,19,[22][23][24][25] But, further research is needed to determine the optimal treatment for reconstruction of chronic distal bicep tendon ruptures. …”
Section: Resultsmentioning
confidence: 98%
“…Bayat et al reported the case of a 50-year-old rock climber sustaining bilateral injuries while climbing, who presented for surgical treatment two years after the injury [2]. He went on to have tendon reconstructions with ipsilateral fascia lata grafts on the right and left, staged six months apart.…”
Section: Discussionmentioning
confidence: 99%
“…However, if the correct diagnosis is delayed, the distal biceps tendon retracts and repairs without interposition grafting may be impossible. Various autologous substances have been used, including fascia lata [5,10], semitendinosus [2,8,9,26], flexor carpi radialis [14,22], and palmaris longus [20]. Allografts also have been used [6,18,21,27].…”
Section: Discussionmentioning
confidence: 99%